Complete mitochondrial genome of Appasus japonicus Vuillefroy, 1864 (Hemiptera: Belostomatidae). Issue 12 (2nd December 2022) - Han, Jung-Soo; Cheon, Kyeong-Sik; Jang, Ji-Eun; Choi, Jun-Kil; Lee, Hwang-Goo
Abstract: We describe the initial sequencing and assembly of the complete mitochondrial genome of Appasus japonicus Vuillefroy, 1864 (Hemiptera; Belostomatidae; Appasus). The mitochondrial genome of A. japonicus was found to be 18, 608 bp. It contains thirteen protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs) and an AT-rich region. The overall base composition of A. japonicus is A-41.9%, C-17.5%, G-11.9%, and T-28.7%. A phylogenetic analysis of 21 species within the order Hemiptera suggests that Diplonychus rusticus is most closely related to A. japonicus .